2016 External Sector Report. (Policy Papers; Policy Paper ;, 2016)
After narrowing in the aftermath of the global financial crisis and remaining broadly unchanged in recent years, global imbalances increased moderately in 2015, amid a reconfiguration of current accounts and exchange rates. Shifts in 2015 were driven primarily by the uneven strength of the recovery in advanced economies, the redistributive effects of the sharp fall in commodity prices, and tighter external financing conditions for emerging markets (EMs). A relatively stronger U.S. outlook led to a further appreciation of the USD and a depreciation of the yen and the euro. The sharp decline in commodity prices, reflecting both supply shocks and concerns about rebalancing and growth in China, brought about a significant redistribution of income from commodity exporters to importers, and a weakening of commodity exporters' currencies. Meanwhile, heightened global risk aversion, contributed to softer capital inflows and depreciation pressures in many EMs. This moderate widening of current account imbalances was largely driven by systemic economies. Surpluses in Japan, the euro area and China grew, supported by improved terms of trade and currency depreciation, while the current account deficit in the U.S. widened amid the steep appreciation of the USD. These widening imbalances were only partially offset by narrowing surpluses in large oil exporters and smaller deficits in vulnerable EMs and some euro area debtor countries. Similarly, excess imbalances expanded in 2015. External positions in the U.S. and Japan moved from being broadly in line with fundamentals to being 'moderately weaker' and 'moderately stronger', respectively. This was partly offset by a further narrowing of excess deficits in vulnerable EMs and euro area debtor countries. Meanwhile, excess surpluses persisted among the larger surplus countries, some of which remain 'substantially stronger' than fundamentals (Germany, Korea). Currency movements since end-2015 helped to partially reverse the trends observed last year, although market volatility following the result of the U.K. referendum to leave the European Union have led to a strengthening of the USD and yen along with a weakening of the sterling, euro, and EM currencies. The implications for external assessments going forward, especially for the U.K. and the euro area, remains uncertain and will likely depend on how the transition is managed and on what new arrangements are adopted. With output below potential in most countries, and limited policy space in many, balancing internal and external objectives will require careful policy calibration. In general, a more balanced policy mix that avoids excessive reliance on policies with significant demanddiverting effects is necessary, with greater emphasis on demand-supportive measures and structural reforms. Surplus countries with fiscal space have a greater role to play in supporting global demand while reducing external imbalances. Global collective policy action, especially if downside risks materialize, would also help address global demand weakness while mitigating its effects on external imbalances.